Geographic variation in the microbiome of Varroa destructor in the neighbouring countries Slovakia and Czechia - Skičková, Štefánia; Baňas, Miroslav; Abuin-Denis, Lianet; Svobodová, Karolína; Maitre, Apolline; Wu-Chuang, Alejandra; Obregón, Dasiel; Mateos-Hernández, Lourdes; Majláth, Igor; Majláthová, Viktória; Krejčí, Alena; Cabezas-Cruz, Alejandro (International microbiology, 2025)
Varroa destructor mite is a major threat to honeybee (Apis mellifera) populations, contributing to colony losses through parasitism and pathogen transmission. While extensive research has focused on Varroa biology and its role as a virus vector, its microbiome remains poorly understood, particularly regarding geographic variation. Here, we investigated the microbial diversity, composition, and functional potential of Varroa mite microbiota collected from two neighboring countries, Czechia and Slovakia. Using high-throughput sequencing and network analysis, we assessed alpha and beta diversity metrics, microbial co-occurrence patterns, and predicted metabolic functions. Our results revealed significant differences in microbial diversity between the two regions, with some bacterial taxa appearing more prevalent in specific populations. Network analysis suggested potential variation in the structural stability of microbial communities in Varroa mites, raising the possibility that geographic factors may influence microbial interactions. Functional profiling indicated region-associated differences in predicted metabolic pathways, possibly linked to certain bacterial taxa. While these findings provide new insights into the Varroa microbiome and its potential ecological role, the interpretation of geographic influence remains a subject of ongoing investigation to better understand its scope and underlying mechanisms. A deeper understanding of these microbial dynamics may contribute to the development of novel strategies for Varroa mite management and the conservation of honeybee health.
Keywords: Microbial co-occurrence networks; Predicted functional pathways; Microbiome; Varroa destructor; Geographical variation